An assessment of reproductive and lifetime performances of Kagoshima Berkshire gilts and sows. (10th November 2013) - Sasaki, Yosuke; Tokunaga, Tadaaki; Uemura, Ryoko; Sueyoshi, Masuo
Abstract We investigated the reproductive and lifetime performances of Kagoshima Berkshire gilts and sows. We examined 20 605 parity records of 4419 pigs for 2008 to 2012 on a farrow‐to‐finish commercial farm. The mean parity (± SD) of all animals was 3.0 ± 2.1. For farrowing performance, the highest numbers of total pigs born and pigs born alive were found in sows with parities 5 and 6 and with parity 3–6, respectively (P < 0.05). Regarding weaning and mating performance, sows with parity 2 had the lowest preweaning mortality (P < 0.05). The longest weaning‐to‐first‐mating interval was found in parity 1 pigs, and the interval decreased as parity increased (P < 0.05). Parities 0 and 1 pigs had the lowest farrowing rate and those with parity 4 had the highest farrowing rate (P < 0.05). The mean parity at culling, total number of pigs born alive in a lifetime, and nonproductive days in a lifetime were 5.5 ± 2.93, 49.2 ± 24.72 pigs, and 132.1 ± 83.34 days, respectively. These animals had a lower litter size and fertility that the F1 crossbred sows mainly used in Japan, but a similar tendency for performance by parity.